The Effect of Game Based Learning Platform on Students Achievement in Autonomous Learning Context: Evidence from EFL Classroom in Pesantren - Devi Nur Aini; Slamet Setiawan; Syafi'ul Anam (ELITE Association Indonesia, 2023)
Abstract. In post pandemic situation, many institutions applied autonomous learning approach in the teaching and learning process. Game has been proved as one of the effective way in improving students mastery of english proficieny. On the other hard, english is a foreign language in indonesia. Many students got difficulty in mastering english subject, they lacked of motivation in learning. Many times, they got bored with the situation in the classroom. The students also depend on the teacher and lecturer when they learn English. To evercome the problem, this study aims to examine the effectiveness of some of the game-based learning platform, in improving students english achievement and their perception toward it. A total of 42 undergraduate students in semester 1 were involved in the study. A one-group pre-test post-test research design was employed with an intervention and autonomous program that spanned 6 weeks. The results was analyzed using non parametric test. The findings showed that game based learning platform that was implemented in the class with the “Quizziz” platform had significant impact in improving students’ English achievement. Keywords: game based learning platform, autonomous learning, students’ achievement